A REVIEW OF THE CREATIVE TEACHING LEARNING PROCESS - Anggraini, Novita Hariana (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
In the world of education teachers play an active role in the teaching process, teachers play a direct role in the field to conduct the learning process. Teachers are also people who must be experts in various fields including shaping the creativity that exists within the educator as well as the learner himself. Educators who have more creativity will make students comfortable in learning so teaching educators is very influential on students' learning achievement. Creative teachers are teachers who can attract students in learning, with creative teachers will not bore students in the learning process. Students will continue to be interested in the learning process from start to finish. Creative teachers will always grow a talent interest in students, always have an open mind and think about the things that will be done in the process of defense. So it is understandable that a creative teacher will think of creative ideas and be implicated in the learning process using media and the like. The learning process requires media that can support the process of learning, without the media used, then the movement space of educators in conducting the learning process will be limited because it is pervasive that no media can be used.